Multimodal analgesia in the postoperative period in patients with abdominal pathology in the Republic of Uzbekistan. - Avakov V.E; Ibragimov N.K.; Ramazanova Z.F.; Muralimova R.S. (Zien Journals, 2022)
Pain is an unpleasant sensory and emotional experience associated with actual or perceived tissue damage. (World Health Organization. International Classification of Diseases 11th Revision. Geneva: World Health Organization; 2019). Postoperative pain of varying intensity occurs after any operation, both after minimal outpatient interventions and after highly traumatic hours-long operations. Postoperative pain is not just an acute pain syndrome, it is also a strong trigger of the surgical stress response, which causes the activation of the autonomic nervous system and has a negative impact on almost all vital organs and systems.
Keywords: pain; analgesia; anesthesia; analgesics